Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/vde.12077
|View full text |Cite
|
Sign up to set email alerts
|

A case in Europe of feline histoplasmosis apparently limited to the skin

Abstract: Histoplasmosis should be included in the differential diagnosis of nodular diseases of cats worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
(20 reference statements)
0
12
0
4
Order By: Relevance
“…Já entre os casos de biopsias, os animais apresentavam lesões de pele e aumento de linfonodos. A alteração macroscópica de pele normalmente está associada com a disseminação do agente (Brilhante et al 2012), embora um estudo indique que a doença possa ocorrer de forma isolada na pele (Fischer et al 2013). A histopatologia e citopatologia são os métodos diagnósticos altamente sugestivos de histoplasmose e as lesões em todos os casos foram semelhantes ao descrito em outros trabalhos para a doença, no qual o agente é visualizado predominantemente no interior de macrófagos (Brömel & Sykes 2005a).…”
Section: Discussionunclassified
“…Já entre os casos de biopsias, os animais apresentavam lesões de pele e aumento de linfonodos. A alteração macroscópica de pele normalmente está associada com a disseminação do agente (Brilhante et al 2012), embora um estudo indique que a doença possa ocorrer de forma isolada na pele (Fischer et al 2013). A histopatologia e citopatologia são os métodos diagnósticos altamente sugestivos de histoplasmose e as lesões em todos os casos foram semelhantes ao descrito em outros trabalhos para a doença, no qual o agente é visualizado predominantemente no interior de macrófagos (Brömel & Sykes 2005a).…”
Section: Discussionunclassified
“…Necropsy of the lung tissue both gross and histopathology samples did not show evidence of granulomatous inflammation or yeast organism. Fisher et al reported a case of feline histoplasmosis limited to the skin [11]. The author suspected that the rapid dissemination of the infectious agents to other organs, such as skin after inhalation, might make it difficult to detect lung lesions on radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Different forms of histoplasmosis, as pulmonary, disseminated, primary gastrointestinal, have been reported in cats (Aulakh et al, 2012). Sometimes the skin is also affected (Fischer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Cats with histoplasmosis normally present anaemia, weight loss, lethargy, fever, anorexia, and interstitial lung disease, but some cases without involvement of the respiratory tract have been reported (Fischer et al, 2013). Less frequent clinical signs include vomiting, diarrhea, blindness and lameness (Brömel e Sykes, 2005;Aulakh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%